تقويم الدليل المحاسبي لحسابات الدولة(*) - شاكر, صلاح صاحب; داخل, عصام حميد (Journal of Economics and Administrative Sciences, 2008)
Evaluation of accounting Guide for State Accounts  The concept of accounting guide for state accounts is to develop government accounting system in Iraq so as meet government wishes, needs and to find an approach of a united accounting. The basic idea of accounting guide for state accounts is to achieve a completion of accounting circulation of a governmental unit which doesn’t have a full accounting circulation. The governmental unit has satisfied with preparing monthly budget reviews, then sending them to the Ministry of finance, and the Ministry on its turn has conducted final calculation preparations on the country's level as a whole. Thus the concept of this research appears.  It is an evaluation of the accounting guide for state accounts. Multiple state accounts, its basic features, its deficiencies as well as weakness will be studied.